Tourism Content Planning Through Digital Marketing: Local Wisdom of Rote Ndao Island, NTT (International Journal of Education and Literature, 2024)
Tourism potential in the East Nusa Tenggara area is one of the owners of diverse natural wealth. This wealth ranges from culture, produce, and processed food to the creative economy. However, it was found that tourism development needs to catch up due to the lack of publications in the digital era. Purpose of the research is to design the preparation of tourism promotion content materials on Rote Ndao island through social media. This study used a descriptive qualitative method. Data collection techniques are carried out by observation, interview, and documentation. Data triangulation methods were used to analyze this study through data reduction, presentation, drawing, and conclusion. The author succeeded in designing a publication content data and Instagram design that can be used as an example or ready-to-use account if we can socialize it. This research focuses only on designing content ideas on Rote Ndao island, East Nusa Tenggara, as a form of caring for local tourism development.